Lenguaje, poder e identidad social. Nietsche, Bordieu, Austin - Yebra López, Carlos (Nómadas. Critical Journal of Social and Juridical Science, 2010)
In this essay, I claim that it is possible to find in Nietzsche's work certain elements that contribute to our understanding of both linguistic and performative turn. Therefore, Austin‟s work systematizes the nietzschean critic to the descriptivist conception of language as well as the fact that the most important aspect is not what we can refer to with words, but what we want to do by using them. Upon the basis of this approach, I understand Bordieu‟s theory with regard to economy of linguistic exchange as allowing us to shed light on the former issue by combining Nietzsche's and Austin's analysis in order to properly depict the link between symbolic power and social legitimation of discourse.
Keywords: Language; Bordieu; power; performativity; Austin